“Engage yourself to a greater cause”: Evaluating the formal internal communications and active listening practices in Talang Dalisay - Tolentino, Clarenz Adrian A. (Animo Repository, 2023)
This study examines engagement amongst volunteer members and the organization called Talang Dalisay, a non-profit organization based in Manila, Philippines, that advocates awareness on mental health issues and illnesses. Guided by the study of Lemon (2019), this study explores the role of organizational communication in active listening and formal internal communication by evaluating the communicative practices enacted in TD. The study utilized a semi-structured interview to gather data and thematic analysis was used to find common themes from the answers of the respondents (n= 12). The identified practices on active listening were Member checkups, Midterm Evaluations and Reciprocal exchanges amongst members. Only downward communication was discovered as the sole formal internal communication practice. Findings suggest that the role of active listening in TD allows members to recognize their voice and be heard. Subsequently, members view the role of formal internal communication as means for them to be involved but this can be overwhelming at times; and functions in a way that is structured and restrictive. The study argues that the relationship of active listening and formal internal communication, as features of dialogue, must coexist to facilitate effective meaning-making processes that underpin engagement.